Study on the influencing factors of effective group cooperation mode in Chinese universities classroom - Pan, Bo; Fatmawati, Latada; Ahmad Muhaimin, Mohamad; Yubo, Shao (Universiti Malaysia Pahang, 2024)
In the 21st century, cooperation ability is crucial for students' employment prospects. Therefore, collaborative group work has become an important part of higher education, yet its effective implementation faces challenges in Chinese universities. Chinese university students have less experience in cooperative learning during their basic education, so it is necessary to identify and optimize the key factors that affect the efficiency of group cooperation. This study focuses on the student factors in effective group cooperation in Chinese universities. After interviewing students in modern educational technology courses, it was found that task allocation, group leader's ability, communication skills, and reward feedback mechanisms are key. In response, it is recommended to allocate tasks clearly and reasonably, select capable group leaders, improve communication skills through training, and establish effective reward mechanisms.